Grading Of Lymphocyte Infiltrating Tumor Can Be Used As A Prognosis Factor Compared To T Pathology And N Pathology On Recurrency Of Colon Cancer - Putu Ayu Saraswati, -
Abstract Background: 30-50% of colon cancer patients will experience recurrence and then die. Several factors that can be used as a prognosis for recurrence are tumor staging, number of lymph nodes resected, high pT, and grading of TILs as an immune response that is useful for suppressing tumor growth. This study aimed to determine whether the TILs grading can be used as a prognostic factor for recurrence than pT and pN.